Human Immunodeficiency Virus Infection and Acquired Immune Deficiency Syndrome in Uganda: A Mini Situational Review - Samuel Kabwigu (HIV/AIDS Research and Treatment-Open Journal, 2023)
Globally, human immunodeficiency virus (HIV) infection is a major public health concern and several countries continuously lay down strategies to contain this pandemic. In Uganda, the government is committed to putting an end to new cases of HIV transmission. According to the latest Joint United Nations Programme on HIV/AIDS (UNAIDS) estimates, since the start of the global HIV/AIDS pandemic, over 75 million people have been infected with HIV and over 32 million people have died from acquired immune deficiency syndrome (AIDS) related illnesses. As of June 2021, UNAIDS estimated that globally, there were about 38 million people living with HIV (PLHIV) with the East and Southern African countries, home to 700 million people, contributing 45%. Uganda has an estimated 1.4 million people living with HIV of which 1.3 million are currently on treatment (Ministry of Health (MoH) Annual Estimates 2021). The country has registered a 37% decline in AIDS annual related deaths, from 27,000 in 2016 to 17,000 in 2021. New HIV infections in 2021 stood at 54,000. This review will highlight some of the efforts put in place to ensure that by 2030 AIDS will not be a public health threat to Ugandans.